Individual participant data meta-analysis: impact of conduct problem severity, comorbid attention-deficit/hyperactivity disorder and emotional problems, and maternal depression on parenting program effects - Leijten, P; Scott, S; Landau, S; Harris, V; Mann, J; Hutchings, J; Beecham, J; Gardner, F (Elsevier, 2020)
Objective There is concern whether established parenting programs for children’s conduct problems meet the needs of families with severe and complex mental health problems. For example, many children with conduct problems show comorbid ADHD or emotional problems, or have parents who are depressed, but families with such complex mental health problems typically seen in real life are often underrepresented in evaluation trials. We tested whether children with more severe conduct problems, and those with more complex mental health problems, benefit less from the Incredible Years parenting program, using individual participant data meta-analysis of randomized trials in Europe.